On Strong NP?(?)-Convergence and S?(?)-Convergence - Kandemir, Hacer Sengul; Cakalli, Huseyin; Et, Mikail (Amer Inst Physics, 2021)
In this paper, we introduce the concept of strong rho-convergence of order beta ( or N-P(beta)(rho) - convergence) of sequence of real numbers and give some inclusion relations between the set of all rho-statistical convergence of order beta and strong N-P(beta)(rho)-convergence.
4th International Conference of Mathematical Sciences (ICMS) -- JUN 17-21, 2020 -- Maltepe Univ, ELECTR NETWORK
Keywords: Statistical convergence; Cestro sununability